Dispute settlement in the World Trade Organization : practice and procedure - Palmeter, N. David; Mavroidis, Petros C.; Meagher, Niall, 1965- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
The WTO dispute settlement process has evolved in recent years into one of the most successful, yet complex, systems of international arbitration. In this extensively revised new edition of Palmeter, Mavroidis, and Meagher's authoritative book on WTO dispute settlement, the authors provide a comprehensive overview of each step of the WTO dispute settlement process, examining both the history of the system, the governing legal rules, and the more informal procedural aspects of the process in detail. This edition takes into account the jurisprudence of panels and the Appellate Body up to the end of 2020 and includes an analysis of the current crisis in the WTO Appellate Body. This volume is an essential tool for practitioners, diplomats, government lawyers, and students of WTO law and should equally be of interest to students of other forms of international arbitration.
Overview -- Jurisdiction -- Sources of law -- Consultations and the panel process -- Special rules and procedures -- Evidence and proof -- The appellate process -- Adoption and implementationof reports -- Remedies -- Conclusion.
Title from publisher's bibliographic system (viewed on 27 Jan 2022).
Keywords: World Trade Organization; Arbitration (International law); Foreign trade regulation; Tariff -- Law and legislation